Pressure and magnetic field-induced transport effects in Ni45.4Mn40In14.6 alloy. (12th October 2021) - Konoplyuk, Sergiy; Kolomiets, Alexandr; Prokleska, Jan; Proschek, Petr; Buturlim, Volodymyr; Gerstein, Gregory; Maier, Hans Jürgen
Abstract: Electrical transport properties were investigated under hydrostatic pressure in the Ni45.4 Mn40 In14.6 alloy. Temperature dependency of electrical resistivity was analysed to find dominant scattering mechanisms and to estimate the volume change during martensitic transformation. The main contributions into electrical resistivity in austenitic phase were found to be scattering by magnetic fluctuations and scattering due to structural disorder. The latter provides significantly higher residual resistivity in comparison with that of the stoichiometric alloy due to irregular positions occupied by excess Mn atoms. The value of volume change upon austenite to martensite transformation was −0.09%. It was found that alloy is characterised by hole conductivity and negative anomalous Hall resistivity, which doubles on application of hydrostatic pressure due to pressure-induced martensitic transformation and reaches the magnitude of 20 μ Ω·cm. The unusual correlation between the Hall and the longitudinal resistivities in the martensitic phase is discussed.